Using Balanced Time Perspective to Explain Well-Being and Planning in Retirement - Mooney, Anna; Earl, Joanne K.; Mooney, Carl H.; Bateman, Hazel (Frontiers in Psychology, 2017)
The notion of whether people focus on the past, present or future, and how it shapes their behaviour is known as Time Perspective. Fundamental to the work of two of its earliest proponents, Zimbardo and Boyd (2008), was the concept of balanced time perspective and its relationship to wellness. A person with balanced time perspective can be expected to have a flexible temporal focus of mostly positive orientations (past-positive, present-hedonistic, and future) and much less negative orientations (past-negative and present-fatalistic). This study measured deviation from balanced time perspective (DBTP: Zhang, Howell, and Stolarski, 2013) in a sample of 243 mature adults aged 45 to 91 years and explored relationships to Retirement Planning, Depression, Anxiety, Stress, Positive Mood, and Negative Mood. Results indicate that DBTP accounts for unexplained variance in the outcome measures even after controlling for demographic variables. DBTP was negatively related to Retirement Planning and Positive Mood and positively related to Depression, Anxiety, Stress and Negative Mood. Theoretical and practical implications regarding balanced time perspective are discussed.